2021
DOI: 10.1530/eje-20-0642
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic and psychological effects of dual-release hydrocortisone: a cross-over study

Abstract: Background: Adrenal insufficiency (AI) is associated with increased cardiovascular morbidity and mortality and reduced quality of life (QoL).Optimum glucocorticoid (GC) dosing and timing are crucial in the treatment of AI, yet the natural circadian secretion of cortisol is difficult to mimic. The once-daily dual-release hydrocortisone (DR-HC) preparation, (Plenadren®), offers a more physiological cortisol profile and may address unmet needs. Methods:An investigator-initiated, prospective, cross-over study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 48 publications
2
12
2
1
Order By: Relevance
“…However, data concerning the role of DR-HC in SAI are scanty, with most studies including retrospective data [11,12] or few patients [9,[13][14][15]. These studies generally report a reduction in BMI and, in some cases, in waist circumference, but they are less consistent on glucose, lipid metabolism and HRQoL improvement [9,[11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, data concerning the role of DR-HC in SAI are scanty, with most studies including retrospective data [11,12] or few patients [9,[13][14][15]. These studies generally report a reduction in BMI and, in some cases, in waist circumference, but they are less consistent on glucose, lipid metabolism and HRQoL improvement [9,[11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies on the use of HC-DR in SAI were few (including retrospective data) [11,12] or small [9,[13][14][15]. These studies generally reported a reduction in BMI and, in some cases, in waist circumference, but they are less concordant with an improvement in glucose and lipid metabolism as well as with HRQoL [9,[11][12][13][14][15][16]. Furthermore, data were biased by the fact that in some studies, the switch from conventional GC therapy to DR-HC involved the transition from clearly supra-physiological to physiological doses [9,11,14,15], and therefore the improvements observed might have been related to the reduction of the dose rather than to the drug formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Bei einmaliger morgendlicher Einnahme von Plenadren kommt es entsprechend zu einer Annäherung an das physiologische Cortisol-Tagesprofil. Bisherige Daten deuten auf günstige Effekte auf das Gewicht, das Lipidprofil, den Blutdruck sowie das Immunsystem nebenniereninsuffizienter Patienten hin 12 13 14 15 16 17 . Eine Umstellung von konventionellem Hydrocortison auf Plenadren ® ist bei Patienten, die mit der Standardtherapie gut zurechtkommen, nicht erforderlich.…”
Section: Therapieunclassified
“…A modified-release hydrocortisone is designed to more closely resemble the physiological cortisol profile (29). This modified hydrocortisone seems to have beneficial effects on the cardiometabolic and immune profile of AI patients compared with hydrocortisone (26,29,30). Furthermore, its improved bioavailability over time leads to ã 20% reduction in the total daily cortisol exposure (29).…”
Section: Adrenal Insufficiencymentioning
confidence: 99%